Cooperative Extension offices as mental health hubs: A social ecological case study in rural Georgia, United States - Virginia Brown; Maria Bowie; Diane Bales; Anna Scheyett; Rebecca Thomas; Georgeanna Cook (Elsevier, 2023)
Rural communities in the U.S. face multiple mental health challenges, with lack of accessible, acceptable services, skepticism towards those outside the community, and stigma towards help-seeking. Mobilizing rural communities to address mental health may be possible if facilitated by a trusted local organization such as Cooperative Extension Service (Extension). Extension promotes community wellbeing through evidence-based programming, extending the reach of land grant universities to local communities. Extension offices are deeply embedded in their communities; personnel are well-known and local residents. In this article we propose a novel model for Extension offices as a trusted place for mental health resource, service, and advocacy hubs, available and accessible to all diverse members of rural communities. Using Social Ecological Theory, we provide examples of how Extension can serve as an integrated hub to help rural communities meet their mental health needs and can be partners and collaborators with mental health providers/agencies.